THE INFLUENCE OF INDEPENDENCE AND MOTIVATION TO LEARN THROUGH PBL ON STUDENTS' PROBLEM-SOLVING ABILITIES - Ali Asmar; Hafizah Delyana (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this research is to find out how the influence of student independence and learning motivation on the problem-solving abilities of Padang State University students in Space Geometry Courses through the Problem Based Learning (PBL) model. The research method used is a survey with correlation and regression analysis. The population in this study was UNP students, with a sample of 23 students with purposive sampling techniques. Data on student independence and learning motivation is obtained through questionnaires. In contrast, the data of problem-solving capabilities are obtained through tests. The results of the data analysis found that the influence of independence and learning motivation on problem-solving ability was shown by a correlation coefficient of 0.642 and a coefficient of determination R2 of 37.8%, and regression line equation Y = 42.271 + 0.334 X1 + 0.404 X2. The testing analysis obtained that the confident correlation and regression coefficient is significant. This research proves that there is an influence of independence and student learning motivation together on students' problem-solving abilities.